Diversity and distribution of the mouse opossums of the genus Thylamys (Didelphimorphia, Didelphidae) in north-eastern and central Argentina - Teta, Pablo Vicente (2009)
Phylogenetic  analysis  of  a  fragment  of  the mitochondrial  genome  and  qualitative  and  quantitative  assessments  of morphological variation suggest that, in its current conception, Thylamys pusillus (Desmarest, 1804) is a complex of at least three species. In the taxonomic arrangement proposed in this work, the populations in the Argentinean provinces of Entre Ríos and Corrientes are here referred to T. citellus (Thomas, 1912), while the small Thylamys that lives in the Argentinean Dry Chaco are provisionally referred to T. pulchellus (Cabrera, 1934). In our scheme, Thylamys pusillus is restricted to the Bolivian and Paraguayan Chaco and the vicinities of northern Formosa province in Argentina. We provide emended diagnosis for T. citellus and T. pulchellus, together with detailed morphological descriptions and discuss their distinctiveness from other species of Thylamys. In addition, we included new distributional data.